Associations between shift work and risk of colorectal cancer in two German cohort studies. (2nd August 2020) - Wichert, Katharina; Rabstein, Sylvia; Stang, Andreas; Erbel, Raimund; Eisele, Lewin; Arendt, Marina; Keimer, Andrea; Dragano, Nico; Hoffmann, Wolfgang; Lerch, Markus M.; Roskoden, Frederick Charles; Schmidt, Carsten Oliver; et al.
ABSTRACT: The association between shift work and the risk of colorectal cancer (CRC) is still unclear. Therefore, we studied the associations between exposure to shift or night work and incident CRC in two German population-based cohort studies, the Heinz Nixdorf Recall Study (HNR) and the Study of Health in Pomerania (SHIP). Including up to 6, 903 participants, we analyzed the cohorts pooled and individually. We estimated incidence rate ratios (IRRs) with adjusted log-linear Poisson regression models with the natural logarithm of person-years as offset and performed subgroup analyses by sex and tumor localization in HNR. The pooled analysis revealed no increased risks for men working in night shifts (IRR: 1.03, 95% CI: 0.62; 1.71). In male HNR participants, we found an increased risk estimate for cancer of the distal colon in shift workers (IRR: 1.60, 95% CI: 0.53; 4.87) and in shift workers who did not perform night work (IRR: 3.93, 95% CI: 0.98; 15.70), but not in night workers. In SHIP, we observed elevated CRC risk estimates for rotating shift work including night work (IRR: 1.45, 95% CI: 0.72; 2.92) and for long-term exposure (IRR: 1.79, 95% CI: 0.81; 3.92) for men. In conclusion, night-shift work was not associated with CRC, although an increased risk was suggested for rotating shift work including nights in SHIP. The heterogeneity of shift-work jobs and schedules and associated lifestyle factors should be taken into account to disentangle a possible relationship between shift work and the risk for CRC in future investigations.